2013
DOI: 10.1007/978-1-4614-7411-1_12
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inner Speech on Arterial CO2 and Cerebral Hemodynamics and Oxygenation: A Functional NIRS Study

Abstract: The aim of the present study was (i) to investigate the effect of inner speech on cerebral hemodynamics and oxygenation, and (ii) to analyze if these changes could be the result of alternations of the arterial carbon dioxide pressure (PaCO2). To this end, in seven adult volunteers, we measured changes of cerebral absolute [O2Hb], [HHb], [tHb] concentrations and tissue oxygen saturation (StO2) (over the left and right anterior prefrontal cortex (PFC)), as well as changes in end-tidal CO2 (PETCO2), a reliable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 14 publications
(18 reference statements)
1
36
0
Order By: Relevance
“…As already indicated in Ref. 9, it is reasonable that the different speech tasks are associated with different characteristics of brain activity. It is, for example, known that mainly stress [35][36][37] and specific types of cognitive processes (particularly memory retrieval and multitasking) 38 are modulating factors for the activity of the PFC.…”
Section: Signal Processing and Statistical Analysismentioning
confidence: 62%
See 3 more Smart Citations
“…As already indicated in Ref. 9, it is reasonable that the different speech tasks are associated with different characteristics of brain activity. It is, for example, known that mainly stress [35][36][37] and specific types of cognitive processes (particularly memory retrieval and multitasking) 38 are modulating factors for the activity of the PFC.…”
Section: Signal Processing and Statistical Analysismentioning
confidence: 62%
“…In a following study, 9 we demonstrated that even inner speech, i.e., speech not spoken aloud, leads to significant changes in P ET CO 2 as well as cerebral hemodynamics and oxygenation. Table 1 gives an overview of previous study results.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Although the light coupling is canceled by the employed self-calibrating algorithm [44], under certain circumstances, light coupling changes still have a small influence on [O2Hb] and [HHb]. On the other hand, such drifts may also reflect real changes in the brain oxygenation, for example caused by transient changes in breathing and/or arterial CO2 [39,68,69], but it is most likely a combination of all these factors. AMARA could have been implemented in a way to eliminate any drifts occurring during a few minutes (e.g., 2 min) after an artifact-but also real signal changes would have been suppressed.…”
Section: Reconstructionmentioning
confidence: 99%